Técnicas de bordado punto smock para la produccion pret a porter de vestidos de niñas de cinco a diez años, aplicado en las estudiantes del 9no. año del centro de formación artesanal Juan Pablo II del cantón Guaranda durante el período 2011- 2012 - Bonilla Roldan, Silvana (2012)
This research work studies the finished didactic techniques of with embroiderings point smock or nest of bee for the production pret to porter of dresses of children. The investigation by means of the survey to the students of the Artisan Center I determine ignorance on the embroidering by hand point smock or commonly call “nest of bee”. Reason for which it will be socialized with the students of ninth.year of the “Juan Pablo II Craft Center” in Guaranda city C with the purpose to cover the emptiness with existing knowledge. Considering that the knowledge on this raised subject is a component important within the industry of the preparation for the innovation and creativity of designs, the learning of this type of embroidering is necessary that can be applied in different articles to dress. From the old times the clothes were distinguished by the varied embroiderings and decorativas applications considering them like true artistic works in some cases of cultural manifestations. The technology and the study have developed new processes of embroiderings by means of the application of suitable sequential systematic techniques that allow improvement of the quality of made articles. Knowing these techniques embroiderings avoids that the work continues being empirical and obtains the improvement of the embroiderings point smock, motivating the creativity of seamstresses and designers. The present competitive market demands the satisfaction of high-priority needs among them the framed clothes but within quality parameters and that this influenced in the fashion and its tendencies. The theoretical content to be developed in this research project will start off with anthropometric basic knowledge, the tendencies for articles to dress its colors and used textiles, the outline of basic landlords and like elementary part the process of embroidering point smock or oriented nest of bee, all these aspects strictly to be applied in the clothes of children. The research methodology will be used critically in order that the work is efficient and it manages to solve the posed problem. The method of study in this research work. will be selected to guarantee obtaining of assertive results to the benefit of the learning and will allow to solve existing values in the students of the Center of Artisan Formation. All contribution to the benefit of the learning contributes to the personal development, acquiring knowledge and to learn every day let grow and allow the development us of society.